Variation in multicomponent recognition cues alters egg rejection decisions: a test of the optimal acceptance threshold hypothesis - Hanley, Daniel; López, Analía V; Fiorini, Vanina D; Reboreda, Juan C; Grim, Tomáš; Hauber, Mark E (Philosophical transactions - Royal Society of London. Biological sciences, 2019)
The optimal acceptance threshold hypothesis provides a general predictive framework for testing behavioural responses to discrimination challenges. Decision-makers should respond to a stimulus when the perceived difference between that stimulus and a comparison template surpasses an acceptance threshold. We tested how individual components of a relevant recognition cue (experimental eggs) contributed to behavioural responses of chalk-browed mockingbirds, Mimus saturninus, a frequent host of the parasitic shiny cowbird, Molothrus bonariensis. To do this, we recorded responses to eggs that varied with respect to two components: colour, ranging from bluer to browner than the hosts' own eggs, and spotting, either spotted like their own or unspotted. Although tests of this hypothesis typically assume that decisions are based on perceived colour dissimilarity between own and foreign eggs, we found that decisions were biased toward rejecting browner eggs. However, as predicted, hosts tolerated spotted eggs more than unspotted eggs, irrespective of colour. These results uncover how a single component of a multicomponent cue can shift a host's discrimination threshold and illustrate how the optimal acceptance threshold hypothesis can be used as a framework to quantify the direction and amount of the shift (in avian perceptual units) of the response curve across relevant phenotypic ranges. This article is part of the theme issue 'The coevolutionary biology of brood parasitism: from mechanism to pattern'.
Keywords: rozhodování; podněty; Cues; Ovum; ovum; rozpoznávání (psychologie); Recognition, Psychology; Songbirds; Animals; Color; vnímání barev; zpěvní ptáci; Color Perception; hnízdění; zvířata; Decision Making; Nesting Behavior; barva